2020
DOI: 10.1088/1674-1056/abad1c
|View full text |Cite
|
Sign up to set email alerts
|

Two-step high-pressure high-temperature synthesis of nanodiamonds from naphthalene*

Abstract: Nanodiamonds have outstanding mechanical properties, chemical inertness, and biocompatibility, which give them potential in various applications. Current methods for preparing nanodiamonds often lead to products with impurities and uneven morphologies. We report a two-step high-pressure high-temperature (HPHT) method to synthesize nanodiamonds using naphthalene as the precursor without metal catalysts. The grain size of the diamonds decreases with increasing carbonization time (at constant pressure and tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…For instance, Lin et al reported the diamond-based photodetectors and their applications in solar-blind imaging , and communication . As the nanometer-sized form of diamond, nanodiamonds (NDs) have received increasing attention owing to their low toxicity, stable fluorescence, facile functionalization, and good biocompatibility. Since the first synthesis of NDs in the 1960s, a large number of studies have already demonstrated their appealing applications in bioimaging, drug delivery, biosensing, and catalysis. However, there are only a few reports on ND materials that applied in photodetection. For example, Jiang et al used NDs to improve the UV detection capability of ZnO nanowires .…”
mentioning
confidence: 99%
“…For instance, Lin et al reported the diamond-based photodetectors and their applications in solar-blind imaging , and communication . As the nanometer-sized form of diamond, nanodiamonds (NDs) have received increasing attention owing to their low toxicity, stable fluorescence, facile functionalization, and good biocompatibility. Since the first synthesis of NDs in the 1960s, a large number of studies have already demonstrated their appealing applications in bioimaging, drug delivery, biosensing, and catalysis. However, there are only a few reports on ND materials that applied in photodetection. For example, Jiang et al used NDs to improve the UV detection capability of ZnO nanowires .…”
mentioning
confidence: 99%
“…There have been some recent reports on HPHT growth of diamond with high phase purity using polycyclic organic compounds such as naphthalene, which also have the potential of heteroatoms doping of diamond. [31,32] In conclusion, we have demonstrated the crystallization of diamond from GO nano sheets using a high temperature/high pressure method, with the XRD and Raman spectra confirming the occurrence of the transition. Moreover, the respective XPS spectra support the observation that the oxygen functional groups of GO are removed, in agreement with the structural phase transition occurring from the initial sp 2 carbon sheet structure to the three-dimensional sp 3 carbon diamond arrangement taking place.…”
mentioning
confidence: 55%
“…Many bottom-up and top-down methods have been developed for the synthesis of NDs that include the detonation of carbon-containing explosives (TNT, RDX, etc.) at high temperatures and pressure under anaerobic conditions, 15 chemical vapor deposition (CVD), 16 microplasma-assisted dissociation of ethanol vapor at atmospheric pressure, 17 chlorination of carbides, 18 ion irradiation of graphite, 19 pulsed laser ablation method (PLA), 20 ultrasound cavitation, 21 high-energy ball milling of diamond microcrystals grown at high pressure and temperature (HPHT), 22 and so forth. Among different methods, only energy-intensive detonation methods are available for the industrial-scale production of NDs.…”
Section: Introductionmentioning
confidence: 99%